High-performance and broadband photodetection of bicrystalline (GaN)1-x(ZnO)x solid solution nanowires via crystal defect engineering; Journal of Materials Science & Technology; Vol. 85 - Ma Zongyi; Li Gang; Zhang Xinglai; Li Jing; Zhang Cai; Ma Yonghui; Zhang Jian; Leng Bing; Usoltseva N. V. Natalia Vasilievna; An V. V. Vladimir Vilorievich; Lyu Baodan (2021, 2021)
Title screen